O impacto do saneamento na taxa de mortalidade infantil: abordagem dos investimentos da CAGECE nos municípios do Ceará - 1997 a 2001 - Ferreira, Clóris Maria Marques (2004)
The correlation between sanitation and health, here represented by the Rate of Infantile Mortality was studied for the municipal districts of Ceará in the period from 1997 to 2001, as a form to measure the impact of the investments of CAGECE in the improvement of the conditions of health of the population. Data of the Rate of Infantile Mortality were used as variable of health and data of Real Connections of Water, real Connections of Sewer, Index of Human Development - Surrenders and Rate of Urbanization as explanatory variables of the model of Multiple Regression, analyzing the municipal districts as a whole and later separating them in two groups in agreement with the level of income, measured by IDH-R. It was going used the method of the Generalized Least Square (Cross Section Weight). The presented results corroborated with the hypothesis that the sanitation constitutes in a generating factor of health and improvement of the life conditions, with satisfactory results for the municipal districts as all, as well as for the groups of lowers income and income average.